Cooperative dissolved organic carbon assimilation by a linuron‐degrading bacterial consortium. Issue 1 (21st November 2012) - Horemans, Benjamin; Vandermaesen, Johanna; Smolders, Erik; Springael, Dirk
Abstract Dissolved organic matter (DOM) is the primary environmental carbon source for heterotrophic bacteria and its quality and quantity have been shown to affect microbial community structure and functioning. In that context, it was examined whether a bacterial consortium synergistically degrading the herbicide linuron extends this synergism toward natural DOM degradation. Biodegradable dissolved organic carbon (BDOC) of DOM of various origins and concomitant growth was determined for the consortium members in isolation and in combination. BDOC decreased with increasing DOM aromaticity, which is a recalcitrance indicator. BDOC in DOM of low aromaticity was 40–50% for all inocula. For DOM with high aromaticity, BDOC decreased with increasing aromaticity and was inoculum dependent, that is, BDOC was > 23% for consortium members in combination compared with BDOC < 16% for isolated strains. The observed BDOC and growth indicated that synergism existed within the consortium for degradation of DOM of both low and high aromaticity. All members benefited from this synergism as growth of all strains increased when incubated in combination, but their relative growth benefit depended on DOM composition. These data suggest that consortia benefit more than individual pesticide degraders from environmental DOM due to cooperation. This is important to understand the effects of DOM on stability and activity of pollutant‐degrading consortia.